A novel approach for congestion control in wireless network - Ishani, Mehta; Kar, Udit Narayan; Gonsai, Dr Atul (IJRDO -Journal of Computer Science Engineering, 2015)
Congestion control in packet switching networks became a high priority in network design and research due to ever-growing network bandwidth and intensive network applications. Dozens of various congestion control strategies have been proposed, and more are forthcoming. Based on control theory concepts congestion control can be viewed as control policy to achieve prescribed goals (e.g., round-trip delay or throughput) in a distributed network environment. This paper discusses the advantages, disadvantages and the applications of various congestion control protocols for wireless networks. It explores the motivation behind the design of congestion control protocols which is suitable to large scale wireless network and abolish drawbacks of the most widely accepted two algorithms of TCP and RCP.